Restoring immune tolerance in pre-RA: immunometabolic dialogue between gut microbiota and regulatory T cells - Gao, Anqi; Wu, Ruihe; Mu, Yanfei; Jin, Ruqing; Jiang, Saixin; Gao, Chong; Li, Xiaofeng; Wang, Caihong (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is a complex chronic autoimmune disease that remains incurable for most patients. With advances in our understanding of the disease’s natural history, the concept of pre-RA has emerged as a window of opportunity to intervene before irreversible joint damage occurs. Numerous studies have indicated that the key step driving autoimmunity in early pre-RA lies at an extra-articular site, which is closely related to the regulatory T (Treg) cell-established immune tolerance to the gut microbiota. The intricate immunometabolic crosstalk between Treg cells and the gut microbiota is beginning to be understood, with the re-recognition of Treg cells as metabolic sensors in recent years. In the future, deciphering their immunometabolic dialogue may help to elucidate the underlying mechanisms of pre-RA. Identifying novel biological pathways in the pre-RA stage will bring insights into restoring immune tolerance, thereby potentially curing or preventing the onset of RA.